Pelaksanaan Pembelajaran Muthola'ah di MA Ibnul Qoyyim Putri Kelas Takhasus - Dewi Nuraeni; Adzfar Ammar (Laboratorium Pendidikan Fakultas Ilmu Tarbiyah dan Keguruan, 2020)
This research is motivated by the lack of reading and translating ability and the lack of utilizing attractive learning methods. Muthola'ah learning requires careful reading skills and Tarjamah learning methods to be able to understand the meaning contained in muthola'ah text. The purpose of this study was to determine the effectiveness of the muthola’ah learning process in the takhasus class in order to be a new reference material for muthola’ah subject teachers at MA Ibnul Qoyyim Putri. This research is a qualitative field research, with data collection methods using observation, interviews, tests, and documentation. The number of students who took the tarjamah test was 18 students. The results showed that the muthola’ah subjects in the takhasus class for the students were, contributing more that with muthola’ah learning could increase students' understanding of Arabic learning, adding vocabulary as provisions to enter the next higher class. The skills achieved with muthola’ah learning include speaking, listening and writing skills. In terms of tarjamah ability, this muthola'ah subject indeed concluded that although teachers often translate from Arabic to Arabic, students can translate into Indonesian with tarjamah lafzhiyah and tahdluriyah types from three written tarjamah tests with the weight of tarjamah question sheets that are different and increase from meeting to meeting. The test results reached an average grade of 95.2. While the tarjamah fauriyah takhasus students test results reached an average grade of 82.8. Keywords: Muthola’ah, Tarjamah, MA Ibnul Qoyyim Putri.